2013
DOI: 10.1039/c3ce41397g
|View full text |Cite
|
Sign up to set email alerts
|

Nucleation kinetics, growth, mechanical, thermal and optical characterization of sulphamic acid single crystal

Abstract: Sulphamic acid (HSO 3 NH 2 ) is a potential material that exhibits excellent piezoelectric and non-linear optical properties.Nucleation and growth kinetics give valuable information about the crystal growth process, which can be employed in the growth of large size crystals. Thus we have studied its nucleation parameters such as solubility, metastable zone width, induction period, interfacial tension, critical free energy, volume free energy change, critical nucleus and found that good quality sulphamic acid c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 27 publications
3
9
0
Order By: Relevance
“…The FWHM of the curve was found to be $8.0 00 , which is close to that expected for an ideal perfect single crystal as predicted by the plane wave theory of dynamical X-ray diffraction (Batterman & Cole, 1964). It is observed that the FWHM of the SA crystal grown by the SRT technique is less than what is typically achieved via the conventional SEST (Jat et al, 2013). This low value of FWHM indicates that the grown SA crystal possesses good crystalline perfection.…”
Section: High-resolution X-ray Diffraction Analysissupporting
confidence: 77%
See 1 more Smart Citation
“…The FWHM of the curve was found to be $8.0 00 , which is close to that expected for an ideal perfect single crystal as predicted by the plane wave theory of dynamical X-ray diffraction (Batterman & Cole, 1964). It is observed that the FWHM of the SA crystal grown by the SRT technique is less than what is typically achieved via the conventional SEST (Jat et al, 2013). This low value of FWHM indicates that the grown SA crystal possesses good crystalline perfection.…”
Section: High-resolution X-ray Diffraction Analysissupporting
confidence: 77%
“…It is a strong inorganic acid, which is moderately soluble in water (Senthil Pandian et al, 2010). Sulphamic acid forms zwitterions when dissolved in water and possesses outstanding catalytic features which make it different from other acidic catalysts (Jat et al, 2013). Because of these advantages, the Japanese Industrial Standards Committee has considered this reagent as a standard substance for titrimetric analysis (Yoshimori & Tanaka, 1973).…”
Section: Introductionmentioning
confidence: 99%
“…This clearly happened owing to significant decrement in the hardness of the title compound with increase in the load. The increasing value of the contact depth h c can also be correlated with the indentation size d. Thus we have a relation between peak load and contact depth as (Jat et al, 2013) …”
Section: Figure 12mentioning
confidence: 99%
“…13(c), the dependence of the stiffness on the contact depth can be observed. The relation of S with h c is given as (Jat et al, 2013) …”
Section: Figure 12mentioning
confidence: 99%
See 1 more Smart Citation